Exploring the Role of Relish on Antimicrobial Peptide Expressions (AMPs) Upon Nematode-Bacteria Complex Challenge in the Nipa Palm Hispid Beetle, Octodonta nipae Maulik (Coleoptera: Chrysomelidae) - Sanda, Nafiu Bala; Hou, Bofeng; Muhammad, Abrar; Ali, Habib; Hou, Youming (Frontiers in Microbiology, 2019)
The humoral immune responses of nipa palm hispid beetle, Octodonta nipae involves the inducible expression of antimicrobial peptide (AMP) genes mediated by immune deficiency signaling pathways. In insects, the nuclear factor-κB (NF‐κB) transcription factor, Relish, was identified to regulate AMP gene expressions upon microbial infections. Here, we dissect the expression patterns of AMPs in O. nipae during infections by entomopathogenic nematodes (EPNs) and their symbionts, before and after Relish knock down. The study results indicate that prior to gene silencing, attacin C1, attacin C2 and defensin 2B were especially expressed to greater extents in symbiotic bacteria, Xenorhabdus nematophila- and Photorhabdus luminescens-challenged insects than in those challenged with Steinernema carpocapsae and Heterorhabditis bacteriophora, with the exception of defensin 2A, which was irregularly expressed. The partial sequence of Relish/NF-κB p110 subunit was confirmed in O. nipae with an open reading frame of 102 amino acid residues. A typical Death domain-containing protein was detected as seen in Drosophila, at the C-terminus of the protein. Phylogenetic analysis showed that Relish of O. nipae was clustered with registered Relish/ NF-κB p110 proteins from other insect species especially Leptinotarsa decemlineata from the same order Coleoptera. The injection of OnRelish dsRNA markedly reduced the expression of OnRelish and decreased the transcription magnitude of attacin C1 and defensin 2B upon S. carpocapsae and H. bacteriophora and their symbionts infections. Altogether, our data confirmed the role of OnRelish as the regulator of AMP genes for immune defense in O. nipae against EPNs and their symbionts.